THE RELATIONSHIP OF FAMILY SUPPORT AND SELF-EFFICACY WITH THE QUALITY OF LIFE OF ELDERLY PEOPLE WITH DIABETES MELLITUS - Rahmi Inayati; Hizir; Marthunis; Teuku Tahlil (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
Elderly is a person who has entered the final phase of life, where almost all the elderly are diagnosed with a disease, one of which is diabetes mellitus. This study aims to find out the relationship between family support, self-efficacy, and the quality of life of elderly people with diabetes mellitus in their area of work, Puskesmas Tangse. The research method uses an analytical survey method with a cross-sectional approach. The population in this study is the total age of people suffering from diabetes mellitus in the working area of Puskesmas Tangse, which is as many as 939 elderly. The sampling technique in this study uses purposive sampling of 100 elderly people. The research was conducted from April to September 2023. The results of this study show that there is a relationship between family support and self-efficacy with the quality of life of elderly people with diabetes mellitus, with a P-value of 0.000. The conclusion of this study is that there is a relationship between family support and self-efficacy and the quality of life of the elderly with diabetes mellitus.